2019
DOI: 10.1111/cpr.12650
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits inflammation and scar formation in the injury tendon healing through regulating JNK/STAT‐3 signalling pathway

Abstract: Objectively: Tendinopathy is a common problem in sports medicine which can lead to severe morbidity. Aspirin, as the classical representative of non-steroidal anti-inflammatory drugs (NSAIDs) for its anti-inflammatory and analgesic actions, has been commonly used in treating tendinopathy. While its treatment effects on injury tendon healing are lacking, illuminating the underlying mechanism may provide scientific basis for clinical treatment. Materials and methods:Firstly, we used immunohistochemistry and qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 43 publications
5
85
0
1
Order By: Relevance
“…In the current study, the biomechanical properties of injury tendon were increased by aspirin treatment, suggesting that aspirin treatment decreased the risk of injury tendon rupture. Our previous study has proved that aspirin improved the biomechanical properties of injury tendon through regulating inflammation and extracellular matrix formation . The present study showed that aspirin reversed the fate of TSCs adipogenic differentiation and inhibited lipids accumulation and infiltration in injury tendon; hence, the biomechanical properties were improved.…”
Section: Discussionsupporting
confidence: 60%
“…In the current study, the biomechanical properties of injury tendon were increased by aspirin treatment, suggesting that aspirin treatment decreased the risk of injury tendon rupture. Our previous study has proved that aspirin improved the biomechanical properties of injury tendon through regulating inflammation and extracellular matrix formation . The present study showed that aspirin reversed the fate of TSCs adipogenic differentiation and inhibited lipids accumulation and infiltration in injury tendon; hence, the biomechanical properties were improved.…”
Section: Discussionsupporting
confidence: 60%
“…Yuan et al () demonstrated that aspirin could promote osteogenic differentiation of human dental pulp stem cells. Interestingly, S. Chen et al () have reported that IL‐6 inhibited tenogenic differentiation via the JAK/STAT‐3 signaling pathway in TSCs, and our previous study has shown that aspirin significantly inhibited expression of IL‐6 (Wang, He, et al, ). Our present study showed that the tendon‐related markers of TNMD, TNC, and SCX were upregulated by aspirin treatment in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…We followed the same methods as in previous studies (Dirks & Warden, ; Wang, He et al, ; Warden, ). A total of 24 male Sprague–Dawley rats were randomly divided into three groups: control group, microdamaged model group, aspirin treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stat3/Stat5 binding sites referred to as STAT-binding elements are usually located in enhancer/promoter regions and first introns of target genes and characterized by clusters of conserved binding motifs with an interferon gammaactivated site-like core sequence (TTCT/CNA/GGAA) (Hutchins et al, 2013;Wingelhofer et al, 2018). It is noteworthy that the activation of JNK/Stat3 signaling has been demonstrated during scar formation as induced by aspirin and was associated with the upregulation of Mrc1 (Wang et al, 2019). Furthermore, an increased expression of Mrc1 in macrophages was accompanied by enhanced Jak2-Stat3 pathway activation (Huang et al, 2019), indicating that Stat3 is a potential positive regulator of Mrc1 expression.…”
Section: Discussionmentioning
confidence: 99%